-2x-18=12+3x

Simple and best practice solution for -2x-18=12+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-18=12+3x equation:


-2x-18=12+3x

We simplify the equation to the form, which is simple to understand
-2x-18=12+3x

We move all terms containing x to the left and all other terms to the right.
-2x-3x=+12+18

We simplify left and right side of the equation.
-5x=+30

We divide both sides of the equation by -5 to get x.
x=-6

See similar equations:

| e^3x=.833333333333 | | 1.66(6x)= | | 1+4x=31 | | 2m^2+17m+22=0 | | 8c-7=5c+2 | | 4(x-y)+7= | | x-15=-3x+13 | | 6e^3x+4=9 | | 3G-22=-4-3g | | 16x^3-10x^2+14x= | | 4p^2-19p-5=0 | | 4(3e-2)=5(e+4) | | -4x+1=-47 | | 11t-13=3t-11 | | 3(4d-2)=5(3-d) | | 16-36-5= | | 28x^2-x-12=0 | | -22=x+-8 | | 6x+5=4-9 | | x+x+9+x+x+5=x+x+x+x+x | | 5(2a-6)=40 | | t-3/2=8/9 | | -25+25+4= | | 2(4x-3.1)=9x-6.2 | | t-3/3=8/9 | | -3+5x=-63 | | 6*11-8=72 | | E-6=-8 | | x^3-4x^2+4x-16= | | 2.7+0.6x=0.3 | | -6+6x=48 | | 1.25r+-7=2.5 |

Equations solver categories